El estudio de las migraciones desde el lugar de origen: razones, significados e incidencia en el desarrollo económico y social. The study of migrations from their place of origin: reasons, significance and impact on economic and social development - Palazuelos, Antonio (Papeles del Este, 2006)
Antonio Palazuelos presents the article “The Study of Migrations from Their Place of Origin: Reasons, Significance and Impact on Economic and Social Development.” In the article, the phenomenon of migrations is studied in a different way from the currents of thought and focuses that in recent years have studied the phenomenon by linking it to economic globalization. Here, migrations are understood as a broad topic that goes beyond economic and social spheres, making this a study of something much more complex. The effects for the exit countries and receiving countries are studied as well as the dynamic of change in the flows. The geographical and thematic range is structured around flows from Latin America towards Spain, and socio-demographic effects are analysed, including the labour area – an escape valve to lower unemployment and real salaries - and the economic factors – remittances - linked to migration and its implications on the economic development of the affected countries.